Giant juvenile ossifying fibroma from diagnosis to management: A rare case - Mokhtar, Ejaz Ahmad; Verma, Sumit; Alam, Shamshad; Fatima, Qalbi (Journal of Medicine and Health Sciences Research, 2020)
Juvenile aggressive ossifying fibroma is a rare, benign tumor of the maxillofacial region that is aggressive and recurrent leading to multiple surgeries causing maxillofacial defect and deformities. The management of patients with ossifying fibroma is controversial. The aim was to report a case of huge ossifying fibroma involving maxilla, zygoma, and orbit in a young female with a duration of 15 years. The patient was operated multiple times but the lesion recurred. Patient-specific implant was fabricated to replace the defect area which would be created after surgery but with meticulous intraoperative decision the high morbid surgery was changed to conservative surgery. No recurrence was seen after two year follow up. The patient aesthetic has also improved. In conclusion it can be said in huge benign ossifying fibroma morbid surgery should be avoided.